Nghiên cứu tính chất điện hoá hệ điện cực nano bạc/bạc oxit trong dung dịch điện ly kiềm - Cương, Bùi Đức; Tùy, Trần Quốc; Hùng, Nguyễn Đức (Vietnam Journal of Chemistry, 2014)
The nano-structure silver electrodes were fabricated using nano-silver powder, carboxymethyl cellulose (CMC) binder and expanded silver metal current collectors. The present paper reports the fabrication, and electrochemical properties of electrodes. The electrochemical properties of the nano Ag/Ag2O, AgO electrode for silver-zinc batteries such as the galvanostatic charge-discharge performance, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were measured. It was found that characteristic and mechanism of the charge-discharge process of silver electrode in KOH electrolyte depends on current density. Keywords: Charge-discharge process, nano Ag/Ag2O, AgO electrodes, electrochemical properties.